Basic Website Creation Training for Muhammadiyah Mamala High School Students in Central Maluku Regency - Citra Fathia Palembang; Mozart Winston Talakua; Zeth Arthur Leleury; Yopi Andry Lesnussa; Francis Yunito Rumlawang; Jefri Esna Thomas Radjabaycolle; Abraham Zakharia Wattimena; Henry Willyam M. Patty (EQUATOR SINAR AKADEMIA, 2022)
The team's implementation of community service activities provides materials and training to Muhammadiyah Mamala High School students on how to easily build a website from the ground up using a content management system (CMS) until the website is successfully uploaded to the Internet (hosting), both for free and for a fee. The goal of this community service activity is for students to gain information technology knowledge that is not limited to being able to access information, but also to being able to create a container/information medium in the form of a website and, hopefully, to help the school in developing the school website in the future